De-escalation of Antibiotics in Respiratory Tract Infection based upon Age, Gender and Culture Report - Anil, Ancy; Anil, Angelin Ann; Wilson, Sharon; Thomas, Tintu; James, Elizabeth; B, Abhilash Kumar (Indian Journal of Pharmacy Practice)
Background: Antibiotic de-escalation is a critical antimicrobial stewardship practice that ensures targeted, safer therapy. However, the influence of patient-specific factors such as age, gender, and microbiological cultures on de-escalation in Respiratory Tract Infections (RTIs) remains underexplored in real-world settings. Objectives: To assess the impact of age, gender, and culture positivity on antibiotic de-escalation timing in patients admitted with respiratory tract infections. Materials and Methods: A retrospective observational study was conducted in the medical wards of a tertiary care hospital in Kerala between January and December 2023. Medical records of 571 patients diagnosed with RTIs and on empirical antibiotic therapy for more than 48 hr were reviewed. Patients were stratified based on age (<60 or ≥60 years), gender, and culture results. Time to antibiotic de-escalation was assessed and compared across these variables. Results: Among 571 patients, 351 (61.5%) were aged <60 years and 220 (38.5%) were aged ≥60 years. The median time to de-escalation in the elderly group was 8 days, compared to 5 days in younger patients (p<0.05). Gender showed no statistically significant difference in de-escalation timing. Out of 571 patients, only 134 (23.5%) had positive cultures. However, culture positivity did not significantly alter de-escalation timelines. Conclusion: Age is a key factor influencing delayed antibiotic de-escalation in respiratory infections, whereas gender and culture positivity had limited impact. These findings highlight the need for tailored de-escalation protocols, especially in elderly patients.
Keywords: Antibiotic De-escalation; Respiratory Tract Infections; Age; Gender; Culture Sensitivity; Antimicrobial Stewardship